(untitled) (Journal of The Colloquium for Information Systems Security Education, 2022)
Advanced persistent threats are causing several serious cybersecurity events due to their highly stealthy characteristics, advanced technology and tools, and complicated attacking strategies, making them an imminent challenge to cybersecurity professionals. To conquer such a challenge, a thorough and dedicated defense plan must be addressed, and we believe engaging advanced persistent threat learning experiences to computer science and cybersecurity students in the early stages of their college education will be the most important part of the plan. Since there is a lack of promising approaches for engaging students in learning of advanced persistent threats, it is now an emerging issue for cybersecurity educators and researchers to investigate and develop doable and affordable advanced persistent threat learning platforms. Hands-on learning has been adopted by several fields and demonstrated promising performance improvements in the learners. Therefore, integrating hands-on learning knowledge and experiences in advanced persistent threat training for computer science and cybersecurity students will be a potential solution for mitigating such an issue. In this research, we recognize the importance of improving students’ learning of advanced persistent threats. To develop a learning platform for students to learn the knowledge, skills, and abilities of advanced persistent threats, we adopt the NDG ethical hacking lab series with appropriate supplemental lectures to each stage of the lifecycle of an advanced persistent threat. We ensure our model could comply with the required knowledge units listed on NICE Cybersecurity Workforce Framework. Students are expected to connect their advanced persistent threat learning experiences to real world cybercrime cases once they have successfully completed the learning process.